Design and development of an unmanned aerial vehicle for agricultural spraying in Brazil - Rasi, Jose Roberto; Mollo Neto, Mario; Bernardo, Roberto (International Journal for Innovation Education and Research, 2020)
This paper presents the development of the unmanned aerial vehicle (UAV) and its configurations as a platform for agricultural sprayers, with a hopper with a capacity of 100 kg, which can perform better maneuvers than conventional agricultural aviation, for precision spraying on small and medium Brazilian properties agricultural. The development and construction focused on precision spray agriculture, taking into account the reduction of costs and accident risks, modernizing, and complementing the activity. Prince Air Models Ltd. made the prototype with resources from FAPESP under Brazilian patent number PI 0404045-7 B1. It presented acceptable results for all flight situations requested with 100 kg of payload and flying in typical maneuvers and agricultural patterns.